Meshing Simulation of Face-Gear Drives using Multibody Dynamics Software. Issue 1 (1st June 2022) - Lee, C K; Hsieh, C L; Lin, P C; Wang, C Y
Abstract: This paper aims to conduct the meshing simulation of two designs of face-gear drives (FGDs) by using the multibody dynamics software, SolidWorks motion. The pinion in the original design of FGD is not provided with any crowning modification, but the pinion in the improved design of FGD is provided with both profile and longitudinal crowning modifications. The results obtained by the meshing simulation show that the edge contact phenomenon greatly reduces the transmission stability of the original design. By giving the pinion a convex dressing in two directions, the transmission stability can be largely improved. The fluctuation in angular velocity and angular acceleration of the improved design of FGD is obviously lower than those of the original design.